The Long Non-coding Road to Atherosclerosis - Josefs, Tatjana (Curr Atheroscler Rep, 2020)
PURPOSE OF REVIEW: To summarize recent insights into long non-coding RNAs (lncRNAs) involved in atherosclerosis. Because atherosclerosis is the main underlying pathology of cardiovascular diseases (CVD), the world’s deadliest disease, finding novel therapeutic strategies is of high interest. RECENT FINDINGS: LncRNAs can bind to proteins, DNA, and RNA regulating disease initiation and plaque growth as well as plaque stability in different cell types such as endothelial cells (ECs), vascular smooth muscle cells (VSMCs), and macrophages. A number of lncRNAs have been implicated in cholesterol homeostasis and foam cell formation such as LASER, LeXis, and CHROME. Among others, MANTIS, lncRNA-CCL2, and MALAT1 were shown to be involved in vascular inflammation. Further regulations include, but are not limited to, DNA damage response in ECs, phenotypic switch of VSMCs, and various cell death mechanisms. Interestingly, some lncRNAs are closely correlated with response to statin treatment, such as NEXN-AS1 or LASER. Additionally, some lncRNAs may serve as CVD biomarkers. SUMMARY: LncRNAs are a potential novel therapeutic target to treat CVD, but research of lncRNA in atherosclerosis is still in its infancy. With increasing knowledge of the complex and diverse regulations of lncRNAs in the heterogeneous environment of atherosclerotic plaques, lncRNAs hold promise for their clinical translation in the near future.